Numerical Simulation of Double-Sided Lid-Driven Cavity Flow Using Moment-Based Boundary Conditions for The Lattice Boltzmann Method - Mohammed, Seemaa A. (Iraqi Journal of Science, 2025)
The present study considers to confirming the applicability of flow with double-sided square lid driven cavity flow by using the lattice Boltzmann equation with moment-based boundary conditions for no slip boundaries. The boundary conditions are applied over the hydrodynamic moments of the lattice Boltzmann equations locally at each node. The investigation is carried out numerically for both single and multiple relaxation time models. To simulate two-sided lid driven-cavity flow, the top and bottom walls are moving with constant velocity while other walls are stationary. Various Reynolds numbers are used in a range of 100 and up to 5000. The present method shows the effect of the moving boundaries on the two symmetrical cavities that is separated by one center line. An expected behavior is achieved here. For validation, a comparison between our method and benchmark data is inserted. The comparison is found in a very good agreement with the literature.